Holy Warriors : The Religious Ideology of Chivalry - Kaeuper, Richard W. (Book collections on Project MUSE., 2009)
Kaeuper argues that chivalric ideology of the high and later Middle Ages selectively appropriated religious ideas to valorize the institution of knighthood. He describes how both elite warriors and clerics contributed to a Christian theology that validated the knights' bloody profession.